Preparation of novel compounds, characterization and studying experimentally and theoretically as inhibitors through thermodynamic and quantum chemistry - Meften, Mushtaq Jerri (European Journal of Chemistry, 2017)
To inhibit corrosion of the mild steel Q235 type in cooling water systems, two heterocyclic compounds were used, namely (3-(2-hydroxy-3-methoxyphenyl)-5-(4-nitrophenyl)-2-(4-((4-nitrophenyl)diazennyl)phenyl)dihydro-2H-pyrrolo[3,4-d]isoxazole-4,6(5H,6aH)-dione) (A1), and (5-(4-(1,3,5-dithiazinan-5-yl)phenyl)-5-pentyl-1,3,5-dithiazinan-5-ium (A2). They were experimentally evaluated by weight loss method at deference concentrations from 1×10-1 M to 1×10-5 M at 5 hours, and theoretically through thermodynamic functions, such as activation energy, standard free energy of adsorption, enthalpy of adsorption and entropy of adsorption. On the other hand, they were theoretically studied through quantum chemistry, such as quantum parameters including Highest occupied molecular orbital )HOMO( energy, Lowest unoccupied molecular orbital (LUMO) energy, energy gap, dipole moment, chemical potential, ΔEBack-donation, global hardness, global softness, global electrophilicity index, ionization potential, electro negativity and number of transferred electrons. The temperature effect on the corrosion rate has been studied at 25, 35, 45, 55 and 65 °C, and the adsorption for studied inhibitors on mild steel surface obeyed Langmuir adsorption isotherm. The methods of compounds preparation A1 and A2 are different from each other, A1 was prepared through several steps, and A2 through the domino reaction (by two step). The results indicate that the studied inhibitors exhibit good performance as an inhibitors for mild steel corrosion in cooling water systems, and inhibition efficiency increasing with increase inhibitors concentration and decreased with temperature rise.